Pengaruh Kepemimpinan, Kepuasan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan Pada PT Akur Pratama Cabang Yogya Riau Junction Bandung - Prayogo, Elia Millenia; Siddiq, Andika Mochamad; Wijaya, Fanji Wijaya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Akur Pratama's branch in Yogya Riau Junction is a retail establishment that operates as a department store or general store. This retail organization needs to support the enhancement of employee performance adequately. The insufficient supervision of superiors over subordinates has led to underwhelming performance, as evidenced by the leadership style employed, employee job satisfaction, and a lack of work discipline. This study assesses the impact of leadership, job happiness, and work discipline on employee performance at PT Akur Pratama Branch at Yogya Riau Junction Bandung. The study methodology is quantitative research, utilizing a descriptive and verification technique. The study sample has a total of 80 participants. The research findings indicate that leadership, job satisfaction, and work discipline favorably influence individual and collective employee performance. Job satisfaction, work discipline, and employee performance. Furthermore, the sample. The research findings indicate that leadership, job satisfaction, and work discipline favorably influence individual and collective employee performance.